FERTILIZANTES FOLIARES E SEUS EFEITOS EM CARACTERES DE PRODUÇÃO EM TRIGO - Valentini, Ana P. F.; Zambonato, Felipe; Wagner, Juliano F.; Antonow, Diovane; Silva, Adair J. d.; Maixner, Adriano R.; Uhde, Leonir T.; Fernandes, Sandra B. V.; Krüger, Cleusa A. M. B.; Silva, Jose A. G. d. (Salão do Conhecimento, 2013)
Resumo